Предмет: Алгебра,
автор: mrvalerikvalerik94
Алгебра 7класс.Упростите выражение1)(2m+3)(4m^2-6m+9)
Ответы
Автор ответа:
0
(2m+3)(4m^2-6m+9) =
(2m)^3+3^3 =
8m^3+27 - ответ используя формулу a^3+b^3 (сумма кубов двух велечин)
(2m)^3+3^3 =
8m^3+27 - ответ используя формулу a^3+b^3 (сумма кубов двух велечин)
Автор ответа:
0
(2m+3)(4m^2-6m+9)=(2m+3)(2m-3)^2=(2m+3)(2m-3)(2m-3)=(4m-9)(2m-3)=8m^2-30m+27
Похожие вопросы
Предмет: Математика,
автор: jedic228
Предмет: Математика,
автор: kamilla457
Предмет: Физика,
автор: uavdeev834
Предмет: Математика,
автор: данька18
Предмет: Математика,
автор: Аноним